Nursing workload in specialized Semi-intensive Therapy unit: workforce size criteria - Trettene, Armando dos Santos; Luiz, Aline Godoi; Razera, Ana Paula Ribeiro; Maximiano, Thaís de Oliveira; Cintra, Flavia Maria Ravagnani Neves; Monteiro, Laressa Manfio (Revista da Escola de Enfermagem da USP, 2015)
OBJECTIVE To assess the nursing workload (NW) in Semi-intensive Therapy Unit, specialized in the care of children with Craniofacial anomalies and associated syndromes; to compare the amount of workforce required according to the Nursing Activities Score (NAS) and the COFEN Resolution 293/04. METHOD Cross-sectional study, whose sample was composed of 72 patients. Nursing workload was assessed through retrospective application of the NAS. RESULTS the NAS mean was 49.5%. Nursing workload for the last day of hospitalization was lower in patients being discharged to home (p